Carbohydrates-rich corncobs supported metal-organic frameworks as versatile biosorbents for dye removal and microbial inactivation. (15th October 2019) - Duan, Chao; Meng, Xin; Liu, Chaoran; Lu, Wanli; Liu, Jun; Dai, Lei; Wang, Wenliang; Zhao, Wei; Xiong, Chuanyin; Ni, Yonghao
Graphical abstract: Highlights: A concept of converting corncobs to versatile biosorbents was proposed. Corncobs serve as supports/ stabilizers for anchoring of MOFs. The biosorbents show effective dyes removal and microbial inactivation. ZIF-8/OCBs have excellent dye adsorption capacity and recyclability. Abstract: In this work, biodegradable cellulose-based biosorbents (MOFs/OCBs) with dual function of dye removal and microbial inactivation were fabricated by in situ anchoring metal-organic frameworks (MOFs) on the TEMPO oxidized corncobs (OCBs). Results showed that delignification and oxidation can develop the OCBs with more cellulose content, carboxyl groups and specific surface area, thus facilitating the deposition of MOFs. The porous and carbohydrate-rich OCBs can serve as supports and stabilizers for MOFs, allowing for enhanced stability and recyclability of MOFs powders. The MOFs, namely HKUST-1 and ZIF-8, can endow the OCBs multiple functions of good adsorption capacity to methyl orange (from 8% of OCBs to 55% of HKUST-1/OCBs and 84% of ZIF-8/OCBs) and excellent antibacterial activity (from 0 of OCBs to 90.2% of HKUST-1/OCBs and 44.8% of ZIF-8/OCBs). Such a concept may offer a new pathway for preparing economical and efficient biosorbents for environmental remedy purposes.